Successful Treatment of Suspected Cannabinoid Hyperemesis Syndrome Using Haloperidol in the Outpatient Setting - Jennifer L. Jones; Karen E. Abernathy (Case Reports in Psychiatry)
Chronic use of cannabis can result in a syndrome of hyperemesis characterized by cyclical vomiting without any other identifiable causes. Cannabinoid hyperemesis syndrome (CHS) is seldom responsive to traditional antiemetic therapies. Despite frequent nausea and vomiting, patients may be reluctant to discontinue use of cannabis. We report a case of severe, refractory CHS with complete resolution of nausea and vomiting after treatment with haloperidol in the outpatient setting. After review of the literature, we believe this is the first reported successful outpatient treatment of CHS and suggests a potential treatment for refractory patients.